Labor-management organizations and their effects on the labor market: evidence from Costa Rican Solidarity Associations - Córdoba Solano, Daniela (2025)
Solidarity associations are a distinctive form of labor-management organization in Costa Rica that has received little scholarly attention. This study examines the relationship between membership in a solidarity association and various labor market outcomes using data from the National Household Surveys (2017–2022). The findings indicate that affiliated individuals earn higher net monthly wages and receive an annual economic surplus of 42% of their net monthly income. Based on an analysis of the 2017–2021 panel data and a Differences-in-Differences model, the results show that affiliation with a solidarity association increases the likelihood of remaining employed, staying in the formal sector, and continuing to participate in the labor market. However, no significant effect on wages is observed. These findings underscore the role of solidarity associations in promoting employment stability and formalization, with implications for both the business sector and the design of public policies to foster their development.